2019
DOI: 10.1016/j.jpsychores.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility of a guided Internet-based intervention in comparison with attention only for people with HIV and depressive symptoms: A randomized controlled trial

Abstract: van den Akker-van Marle , Cost-utility of a guided Internetbased intervention in comparison with attention only for people with HIV and depressive symptoms: A randomized controlled trial. Psr (2019),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Four guided [53][54][55][56] IMIs, compared with WLC, were considered cost-effective (<£30,000 per QALY gained, probabilities ranging from 55 53 to 98% 55 ) from the societal and healthcare perspective. Results of the cost-effectiveness analyses were unclear 54 or showed a low likelihood of being cost-effective at a WTP of nil from a societal perspective (CEA = 30-38% 53 ).…”
Section: Mddmentioning
confidence: 99%
“…Four guided [53][54][55][56] IMIs, compared with WLC, were considered cost-effective (<£30,000 per QALY gained, probabilities ranging from 55 53 to 98% 55 ) from the societal and healthcare perspective. Results of the cost-effectiveness analyses were unclear 54 or showed a low likelihood of being cost-effective at a WTP of nil from a societal perspective (CEA = 30-38% 53 ).…”
Section: Mddmentioning
confidence: 99%
“…Only three out of the 29 studies explicitly reported to have undertaken a CUA [ 35 37 ] and one study was explicit about having conducted both a CEA and CUA [ 38 ]. Modelling was used in all but two studies, which were trial-based [ 36 , 37 ]. Most of the modelling studies applied a (dynamic) transmission model, which is the preferred method when evaluating infectious diseases [ 39 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vaccination and screening interventions dominated, and involved stand-alone vaccination [ 45 , 50 52 ], vaccination in addition to screening [ 40 , 53 56 ], vaccination of girls and boys [ 43 , 47 ], sex-neutral vaccination [ 49 ], screening (stand-alone) [ 41 , 57 59 ], screening in addition to testing [ 60 ] and screening after vaccination [ 61 ]. Other interventions involved test and treat interventions including PrEP (Pre-Exposure Prophylaxis) [ 42 , 62 ], testing and linkage to care [ 37 ] and opt-out testing strategy [ 46 ]; expedited partner treatment [ 46 ], population-level treatment expansion [ 44 ], (on-demand) PrEP [ 35 , 63 ], treatment adherence interventions [ 38 ], guided internet-based behaviour intervention [ 36 ] and financial incentives [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations